Polyethylene resin composition for ultra-pure water piping material

CN115552161BActive Publication Date: 2026-10-16SEKISUI CHEMICAL CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180024070.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-16
Filing Date
2021-03-09
Publication Date
2026-10-16
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

[0007]目前,随着半导体芯片的集成度提高,电路图案越来越微细化,也更容易受低水平的杂质影响

Benefits of technology

[0042] According to the present invention, it is possible to provide a piping material for ultrapure water that reduces calcium leaching and has mechanical properties, and a polyethylene resin composition for ultrapure water piping material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115552161B_ABST
    Figure CN115552161B_ABST
Patent Text Reader

Abstract

The pipe (10) has a polyethylene-based resin layer (21) that contains a polyethylene-based resin composition as a main component. The polyethylene-based resin layer (21) forms a pipe material inner surface (10a). The polyethylene-based resin composition has a calcium concentration of 10 ppm or more and 60 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a piping material for ultrapure water and a polyethylene resin composition for use in ultrapure water piping materials. More specifically, this invention relates to a polyethylene resin pipe / fitting / valve, etc., used as a piping material for ultrapure water, and a polyethylene resin composition for use in ultrapure water piping materials. Background Technology

[0002] Previously, ultrapure water purified to extremely high purity was used in the wet cleaning process when manufacturing precision devices such as semiconductor devices or liquid crystal display devices. If metal ions or other metals are present in the water at concentrations exceeding a certain level, the metals may adsorb onto the wafer surface, which can adversely affect the quality of the precision device. Therefore, it is necessary to strictly limit the impurities in ultrapure water.

[0003] Impurities can also be introduced into ultrapure water in the piping of the ultrapure water delivery lines. While stainless steel and other metals with excellent gas barrier properties are sometimes used as materials for piping, resin is considered preferable due to the potential for metal leaching from the piping.

[0004] Regarding the resins used in piping materials for ultrapure water, fluoropolymers have consistently been used, which are chemically inert, have gas-barrier properties, and exhibit minimal solubility in ultrapure water. For example, fluoropolymer double-layer pipes, consisting of two layers of fluoropolymer, are used in piping systems for semiconductor manufacturing and liquid crystal manufacturing. Examples of fluoropolymer double-layer pipes include those where the inner layer contains a fluoropolymer with excellent corrosion resistance and chemical resistance (e.g., tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), or tetrafluoroethylene-ethylene copolymer (ETFE)), and the outer layer contains a fluoropolymer that inhibits gas permeation (e.g., polyvinylidene fluoride (PVDF)).

[0005] Furthermore, Patent Document 1 discloses a multilayer pipe characterized in that it is a multilayer pipe for ultrapure water piping, and comprises: a first resin layer containing fluoropolymer and in contact with ultrapure water, and a second resin layer containing non-permeable resin and disposed on the outer peripheral surface of the first resin layer. Patent Document 1 also discloses that a third resin layer protecting the second resin layer is further disposed on the outer peripheral surface of the second resin layer, and that polyethylene is used as the third resin layer.

[0006] Among the resins used in piping materials for ultrapure water, polyvinylidene fluoride (PVDF) is particularly widely used in the semiconductor field. It is applied in all piping systems used in ultrapure water manufacturing plants to transport ultrapure water from the manufacturing plant to the point of use, and has become the technical standard for piping materials for ultrapure water.

[0007] Currently, with the increasing integration of semiconductor chips and the increasingly finer circuit patterns, they are more susceptible to the effects of even low-level impurities. Therefore, the water quality requirements for ultrapure water are becoming increasingly stringent. For example, SEMI F75 publishes standards regarding the quality of ultrapure water used in semiconductor manufacturing, which is updated every two years.

[0008] Existing technical documents

[0009] Patent documents

[0010] [Patent Document 1] Japanese Patent Application Publication No. 2010-234576 Summary of the Invention

[0011] The technical problem that the invention aims to solve

[0012] Compared to other common piping, fluoropolymer piping such as PVDF has disadvantages in terms of workability and cost. However, with increasingly stringent requirements for ultrapure water quality, fluoropolymer piping is practically the only option to meet these requirements.

[0013] The inventors specifically focused on materials that could replace piping materials for ultrapure water. For example, polyethylene resins, which offer excellent workability and cost-effectiveness, are commonly used as piping materials. However, polyethylene resins, widely used as piping materials, are synthesized through polymerization using chlorine-based catalysts such as Ziegler catalysts. After polymerization, neutralizing agents such as calcium stearate are mixed in to neutralize catalyst residues. Furthermore, in these neutralizing agents, fatty acid metal soaps such as calcium stearate not only neutralize chlorine but also act as lubricants for molds. Therefore, regardless of the type of polymerization catalyst used for polyethylene, it is typically mixed into the piping material as a surface smoothing modifier. Consequently, in ordinary polyethylene resin pipes, a large amount of calcium from the neutralizing agent dissolves into the water being transported, resulting in water quality far below the requirements for ultrapure water.

[0014] The purpose of this invention is to provide a piping material for ultrapure water that reduces calcium leaching and has sufficient mechanical properties as a pressure piping system, and a polyethylene resin composition for ultrapure water piping material.

[0015] Technical means to solve the problem

[0016] The inventors conducted intensive research and found that, regarding polyethylene resin piping materials, by controlling the calcium concentration of the polyethylene resin in contact with ultrapure water on the inner wall side of the piping material within a specific range and adding phenolic antioxidants, the amount of calcium leaching can be significantly suppressed by limiting its structure to a specific type, and long-term strength can be exhibited; thus, the present invention was completed.

[0017] That is, the present invention provides an invention in the form described below.

[0018] The first type of ultrapure water piping material has a layer mainly composed of polyethylene resin, and the layer forms the inner surface of the piping material, with a calcium concentration of 10 ppm to 60 ppm.

[0019] The piping material for ultrapure water in the second form is the same as the piping material for ultrapure water in the first form, wherein the polyethylene resin is a polyethylene resin obtained by polymerization using a Ziegler catalyst.

[0020] The third type of ultrapure water piping material is the same as the first or second type of ultrapure water piping material, with an antioxidant in its middle layer.

[0021] The fourth type of ultrapure water piping material is the same as the third type of ultrapure water piping material, wherein the antioxidant includes phenolic antioxidants that do not have oxygen derived from phenol groups.

[0022] The fifth type of ultrapure water piping material is the same as the fourth type of ultrapure water piping material, wherein the antioxidant includes a phenolic antioxidant having oxygen derived from a group other than a phenolic group, and the calcium concentration in the layer is less than 50 ppm.

[0023] The sixth type of ultrapure water piping material is any of the first to fifth types of ultrapure water piping materials, the middle layer of which does not actually contain light stabilizers.

[0024] The seventh type of ultrapure water piping material is any of the first to sixth types of ultrapure water piping material, wherein the oxidation induction time of the middle layer at 210°C is more than 20 minutes.

[0025] Type 8 ultrapure water piping material is any of the types 1 to 7 of ultrapure water piping material, wherein the total organic carbon content dissolved from the layer is 30000 μg / m 2 the following.

[0026] The piping material for ultrapure water in Form 9 is any of the piping materials for ultrapure water in Forms 1 to 8, wherein the thickness of the middle layer is 0.3 mm or more.

[0027] The piping material for ultrapure water of type 10 is any of the piping materials for ultrapure water of types 1 to 9, wherein the thickness of the layer is less than 2.0 mm.

[0028] The 11th type of ultrapure water piping material is any of the 1st to 10th types of ultrapure water piping material, which can withstand a circumferential stress of 5.0 MPa at 80°C for more than 3000 hours without damage.

[0029] The polyethylene resin composition for ultrapure water piping material of the 12th type contains polyethylene resin and satisfies the following characteristics (1) to (5).

[0030] Characteristic (1): Melt flow rate (MFR) at 190℃ and 21.6kg load 21.6 The dosage is 6g / 10 minutes or more and 25g / 10 minutes or less.

[0031] Feature (2): MFR 21.6 The ratio of the melt flow rate (MFR5) to the melt flow rate at a load of 5 kg is called FR(MFR). 21.6 / MFR5) is above 25 and below 60.

[0032] Characteristic (3): Contains high molecular weight component (A) and low molecular weight component (B), MFR of high molecular weight component (A) 21.6 The content of α-olefins other than ethylene is 0.05 g / 10 min to 1.0 g / 10 min, and the content of α-olefins other than ethylene is 0.8 mol% to 2.0 mol%, and the content ratio relative to the total resin is 35 wt% to 50 wt%. The melt flow rate (MFR) of the low molecular weight component (B) at a temperature of 190°C and a load of 2.16 kg is... 2.16 The recommended serving size is 20g / 10 minutes or more, or 500g / 10 minutes or less.

[0033] Characteristic (4): Density is 0.946 g / cm³ 3 Above 0.960 g / cm 3 the following.

[0034] Characteristic (5): Calcium concentration is above 10ppm and below 60ppm.

[0035] The polyethylene resin composition for ultrapure water piping material of form 13 is the same as the polyethylene resin composition for ultrapure water piping material of form 12, wherein the polyethylene resin is a polyethylene resin obtained by polymerization using a Ziegler catalyst.

[0036] The polyethylene resin composition for ultrapure water piping materials of type 14 is the same as the polyethylene resin composition for ultrapure water piping materials of type 12 or 13, and contains an antioxidant.

[0037] The polyethylene resin composition for ultrapure water piping material of form 15 is the same as the polyethylene resin composition for ultrapure water piping material of form 14, wherein the antioxidant comprises a phenolic antioxidant that does not have oxygen derived from phenolic groups.

[0038] The polyethylene resin composition for ultrapure water piping material of Form 16 is the same as the polyethylene resin composition for ultrapure water piping material of Form 14, wherein the antioxidant comprises a phenolic antioxidant having oxygen derived from a group other than a phenolic group, and the calcium concentration is less than 50 ppm.

[0039] The polyethylene resin composition for ultrapure water piping material of form 17 is any of the polyethylene resin compositions for ultrapure water piping material of forms 12 to 16, and it does not actually contain light stabilizers.

[0040] The polyethylene resin composition for ultrapure water piping material of form 18 is any of forms 12 to 17, wherein the oxidation induction time at 210°C is 20 minutes or more.

[0041] Invention Effects

[0042] According to the present invention, it is possible to provide a piping material for ultrapure water that reduces calcium leaching and has mechanical properties, and a polyethylene resin composition for ultrapure water piping material. Attached Figure Description

[0043] Figure 1 A schematic cross-sectional view of a pipe, illustrating an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0044] Figure 2 A schematic cross-sectional view of a pipe illustrating another example of a piping material for ultrapure water according to an embodiment of the present invention.

[0045] Figure 3A A diagram showing a connector of an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0046] Figure 3B A diagram showing a connector of an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0047] Figure 3C A diagram showing a connector of an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0048] Figure 3D A diagram showing a connector of an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0049] Figure 3E A diagram showing a connector of an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0050] Figure 4 A diagram of a valve illustrating an example of a piping material for ultrapure water according to an embodiment of the present invention.

[0051] Figure 5 This is the structural formula for Irganox1010.

[0052] Figure 6 The structural formula for Irganox 1330 is given. Detailed Implementation

[0053] The following describes the piping materials for ultrapure water according to embodiments of the present invention. Here, "piping materials for ultrapure water" refers to the general term for components constituting ultrapure water piping, including pipes, connectors, valves, etc.

[0054] [The structure of the pipe]

[0055] The tube of this embodiment will be described below.

[0056] The pipe of this embodiment has a polyethylene resin layer forming the inner surface of the pipe, and the polyethylene resin is the main component. Alternatively, a coating resin layer may be provided on the outer side of the polyethylene resin layer as needed.

[0057] Figure 1 This is a schematic cross-sectional view illustrating an example of the tube in this embodiment. Figure 2 This is a schematic cross-sectional view illustrating another example of the tube in this embodiment.

[0058] Figure 1 The pipe 10 shown (an example of piping material for ultrapure water) has a polyethylene resin layer 21 (an example of a layer). Figure 2 The pipe 11 shown (an example of piping material for ultrapure water) has a polyethylene resin layer 21 forming the innermost layer and a coating resin layer 22 disposed on the outer side thereof.

[0059] Figure 1 The pipe 10 shown is formed of a polyethylene resin layer 21. The polyethylene resin layer 21 forms the inner surface 10a of the pipe 10 (an example of the inner surface of a piping material). Furthermore, Figure 1 The outer surface 10b of the tube 10 shown is also formed of a polyethylene resin layer 21. The polyethylene resin layer 21 is formed in a cylindrical shape in a manner that constitutes the tube 10.

[0060] also, Figure 2 In the pipe 11 shown, a polyethylene resin layer 21 forms the inner surface 11a of the pipe 11 (an example of the inner surface of a piping material). Figure 2 In the tube 11 shown, the outer surface 11b is formed by a coating resin layer 22. The polyethylene resin layer 21 is formed in a cylindrical shape to constitute the innermost layer of the tube 11. The coating resin layer 22 is formed in a cylindrical shape to cover the polyethylene resin layer 21.

[0061] also, Figure 2In the tube 11 shown, only one layer of coating resin 22 is provided on the outside of the polyethylene resin layer 21, but the number of coating resin layers 22 is not particularly limited, and can be one layer or two or more layers.

[0062] The inner surfaces 10a and 11a face the internal flow paths 10c and 11c of tubes 10 and 11, and can also be considered as surfaces that may come into contact with ultrapure water.

[0063] [Connector Composition]

[0064] The connector of this embodiment will be described below.

[0065] The type of connector in this invention is not particularly limited, and examples include: sockets, elbows, T-joints, flanges, etc.

[0066] Figures 3A-3E This diagram illustrates an example of the connector in this embodiment.

[0067] Figure 3A The connector 31 shown is a socket into which tubes are inserted from both ends, connecting the two tubes in a straight line. Connector 31 is, for example, an electrofusion connector.

[0068] Figure 3B The connector 32 shown is an elbow, for example, connecting the pipe at a right angle.

[0069] Figure 3C The connector 33 shown is a T-shaped connector. Connector 33 connects three pipes at 90-degree intervals.

[0070] Figure 3D The connector 34 shown is a flange. The connector 34 has a collar portion 34d and is connected to a valve, etc.

[0071] Figure 3E The connector 35 shown is a reducing connector. Connector 35 connects two pipes of different diameters in a straight line.

[0072] Figures 3A-3E The joints 31 to 35 shown can be constructed using the aforementioned pipe structure, and their cross-sectional shape is the same as that of the aforementioned pipe structure (see reference). Figure 1 and Figure 2 The same applies. That is, each of the connectors 31 to 35 has a polyethylene resin layer 21 forming an inner surface 31a to 35a facing the flow path. Alternatively, a coating resin layer 22 may be provided on the outside of the polyethylene resin layer 21.

[0073] [Valve Composition]

[0074] The valve of this embodiment will be described below.

[0075] The valve used in this embodiment is not particularly limited, and examples include: diaphragm valve, ball valve, butterfly valve, gate valve, check valve, etc.

[0076] Figure 4 A diagram showing a butterfly valve as an example of a valve. Figure 4 The butterfly valve 40 shown includes a valve cage 41, a valve seat ring 42, a valve stem (not shown), a valve body 43, and a handle 44. The valve cage 41 is disposed between pipe components through which fluid flows. A through hole is formed in the valve cage 41. The valve seat ring 42 is mounted on the inner circumferential surface of the through hole in the valve cage 41. The valve body 43 is fixed to the valve stem and rotates together with the valve stem, compressing the valve seat ring 42, thereby blocking the flow path 41a formed on the inner side of the valve seat ring 42. It should be noted that the valve stem is rotated by rotating the handle 44.

[0077] The valve seat ring 42 described above can be constructed using the same tube as described above, with the same cross-sectional shape (see reference). Figure 1 and Figure 2 The same applies. That is, the valve seat ring 42 has a polyethylene resin layer 21 forming an inner surface 42a facing the flow path 41a. A coating resin layer 22 may also be provided on the outside of the polyethylene resin layer 21.

[0078] [Polyethylene resin layer]

[0079] The polyethylene resin layer 21 (an example of a layer) contains polyethylene resin as a main component. The main component refers to the component with the highest content by mass. The main component refers to the component with a content of at least 50%. The lower limit of the polyethylene resin content in the polyethylene resin layer is preferably 50% by mass, more preferably 70% by mass, even more preferably 80% by mass, sometimes even more preferably 90% by mass, and sometimes even more preferably 95% by mass.

[0080] Polyethylene resins can also be copolymerized with α-olefins as needed. Examples of α-olefins that can be copolymerized with polyethylene resins include: propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-butene-1-hexene, 1-butene-4-methyl-1-pentene, 1-butene-1-octene, etc.

[0081] Polyethylene resins are obtained by polymerization using a catalyst containing one or more transition metal derivatives. From the viewpoint of ensuring long-term durability, a Ziegler catalyst is used for polymerization in this embodiment. When polymerizing polyethylene resins using a Ziegler catalyst, a chlorinated catalyst is used in an amount suitable for determination by those skilled in the art, and multi-stage polymerization is carried out. Afterward, a neutralizing agent for neutralizing the chlorinated catalyst is added, and preferably an antioxidant is also added.

[0082] The Ziegler catalyst used in this invention is a well-known catalyst, such as the catalyst system described in Japanese Patent Application Publication Nos. 53-78287, 54-21483, 55-71707, and 58-225105.

[0083] Specifically, a catalyst system comprising a solid catalyst component and an organoaluminum compound can be cited. The solid catalyst component is obtained by co-pulverizing an aluminum trihalide, an organosilicon compound having Si-O bonds, and a magnesium alkoxide to obtain a co-pulverized product, and then contacting a tetravalent titanium compound with the co-pulverized product to obtain the solid catalyst component.

[0084] The solid catalyst preferably contains 1 to 15% by weight of titanium atoms. As an organosilicon compound, preferred examples include organosilicon compounds containing phenyl or aralkyl groups such as diphenyldimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, triphenylethoxysilane, and triphenylmethoxysilane.

[0085] When manufacturing the co-pulverized product, the ratio of aluminum trihalide to organosilicon compound is typically 0.02 to 1.0 mol, preferably 0.05 to 0.20 mol, relative to 1 mol of magnesium alkoxide. Furthermore, a ratio of aluminum atoms in aluminum trihalide to silicon atoms in the organosilicon compound of 0.5 to 2.0 mol is preferable.

[0086] To produce the co-pulverized product, a rotary ball mill, vibratory ball mill, or colloid mill, commonly used in the manufacture of such solid catalyst components, can be employed using conventional methods. The resulting co-pulverized product typically has an average particle size of 50–200 μm and a specific surface area of ​​20–200 m². 2 / g.

[0087] The co-pulverized product obtained in the above manner is brought into liquid phase contact with a tetravalent titanium compound to obtain a solid catalyst component. The organoaluminum compound used in combination with the solid catalyst component is preferably a trialkylaluminum compound, such as triethylaluminum, tri-n-propylaluminum, tri-n-butylaluminum, triisobutylaluminum, etc.

[0088] Examples of neutralizing agents include fatty acid metal salts such as calcium stearate, zinc stearate, and magnesium stearate, as well as hydrotalcites.

[0089] However, when using magnesium stearate or hydrotalcite as a neutralizing agent to polymerize polyethylene resins, if the resulting resin is molded into piping material, a large amount of aluminum or magnesium will dissolve into the water, so this embodiment is not preferred.

[0090] In contrast, when using calcium stearate as a neutralizing agent for the polymerization of polyethylene resins, the above-mentioned aluminum or magnesium metals will not be leached, and good low leaching properties can be obtained. Therefore, calcium stearate is the preferred neutralizing agent in this embodiment.

[0091] From the viewpoint of achieving sufficient pressure resistance to water pressure during water delivery and further reducing pipe wall thickness, high-density polyethylene (HDPE) is preferred as the polyethylene resin composition. From the viewpoint of ensuring the long-term durability of piping materials for ultrapure water, HDPE classified as PE100 or higher in ISO 9080, ISO 1167, and ISO 12162 is more preferred. Furthermore, among HDPEs classified as PE100 or higher, HDPEs with high flowability are preferred to further improve the safety of the piping system, resulting in higher resistance to low-speed crack growth (low-speed crack growth resistance) and better smoothness of the inner surface of the piping. It should be noted that low-speed crack growth refers to the damage caused by damage to the piping material or stress concentration at the joint between the pipe and the fitting.

[0092] As an index for polyethylene resin compositions that meet a pressure resistance level of PE100 or higher and have good flowability, specifically, the melt flow rate (MFR) of the polyethylene resin composition at a temperature of 190°C and a load of 21.6 kg is preferred. 21.6 The melt flow rate (MFR5) at a temperature of 190℃ and a load of 5kg is 6g / 10min to 25g / 10min. 21.6 The ratio of FR (MFR) 21.6 The MFR5 value is between 25 and 60, and the density is 0.946 g / cm³. 3 Above 0.960 g / cm 3 the following.

[0093] MFR in polyethylene resin compositions 21.6 At concentrations below 6g / 10 minutes, the resin material exhibits lower flowability, reduced mold transferability, and insufficient smoothness of the piping inner surface. On the other hand, in MFR... 21.6 At concentrations exceeding 25 g / 10 minutes, it becomes difficult to achieve resin designs that meet PE100 requirements. Furthermore, with a flow rate (FR) less than 25, the narrower molecular weight distribution of the polyethylene resin composition makes it challenging to simultaneously achieve the target MFR. 21.6 With resistance to low-speed crack growth. On the other hand, when FR exceeds 60, there is a risk of reduced impact resistance in polyethylene resin compositions, compromising the safety of piping materials. Regarding density, it is less than 0.946 g / cm³. 3In cases where the density exceeds 0.960 g / cm³, the compressive strength decreases, making it difficult to achieve PE100. On the other hand, when the density exceeds 0.960 g / cm³... 3 In such cases, the safety of the piping system decreases due to the reduced resistance to low-speed crack growth of the piping material.

[0094] Furthermore, the resin composition used to achieve the above-mentioned polyethylene resin composition is preferably composed of multiple components including a high molecular weight component (A) and a low molecular weight component (B).

[0095] MFR of high molecular weight component (A) 21.6 The content of α-olefins other than ethylene is 0.05 g / 10 min to 1.0 g / 10 min, preferably 0.1 g / 10 min to 0.5 g / 10 min, and the content of high molecular weight component (A) relative to the total resin composition is 35 wt% to 50 wt%, preferably 37 wt% to 43 wt%. On the other hand, the melt flow rate (MFR) of low molecular weight component (B) at a temperature of 190°C and a load of 2.16 kg is... 2.16 The dosage is 20g / 10 minutes or more and 500g / 10 minutes or less, preferably 50g / 10 minutes or more and 300g / 10 minutes or less.

[0096] In the high molecular weight component (A) constituting the polyethylene resin composition, MFR 21.6 In order to achieve the target MFR, at a rate of less than 0.05g / 10 minutes. 21.6 This necessitates increasing the MFR (Mean Friction Rate) of the low molecular weight component. However, in this case, the viscosity difference between the high and low molecular weight components during melting increases, reducing compatibility. Consequently, the inner surface of the piping becomes rough due to a decrease in various mechanical properties, including resistance to slow crack growth, or flow instability. On the other hand, in MFR... 21.6 When the concentration exceeds 1.0 g / 10 minutes, various mechanical properties decrease, especially the resistance to low-speed crack growth. Regarding α-olefin content, when it is less than 0.8 mol%, the resistance to low-speed crack growth decreases; when it exceeds 2.0 mol%, the rigidity of the polyethylene resin composition decreases, making it difficult to achieve a resin design that meets PE100 standards. Regarding the content of high molecular weight component (A), when it is less than 35 wt%, the durability of the piping decreases; when it exceeds 50 wt%, the rigidity of the polyethylene resin composition decreases, making it difficult to achieve a resin design that meets PE100 standards.

[0097] When the MFR2 of the low molecular weight component (B) constituting the polyethylene resin composition is less than 20 g / 10 min, the flowability of the polyethylene resin composition decreases, thus reducing mold transferability and resulting in insufficient smoothness of the inner surface of the piping. On the other hand, when the MFR... 2.16 When the pressure exceeds 500g / 10 minutes, various mechanical properties decrease, especially impact resistance.

[0098] It should be noted that the α-olefin content referred to here includes not only the α-olefins supplied to the reactor during polymerization and undergoing copolymerization, but also short-chain byproducts (such as ethyl and methyl branches). The α-olefin content is determined by 13C-NMR (nuclear magnetic resonance). The α-olefin content can be increased or decreased by adjusting the amount of α-olefins supplied for copolymerization with ethylene.

[0099] The calcium concentration of the polyethylene resin layer 21 is 60 ppm or less, preferably 55 ppm or less, and more preferably 50 ppm or less. If the calcium concentration exceeds 60 ppm, the amount of calcium dissolved in the ultrapure water becomes excessive, and the required quality of the ultrapure water cannot be met.

[0100] From the viewpoint of further suppressing the amount of calcium leached in ultrapure water, the calcium concentration of the polyethylene resin layer 21 is preferably as small as possible. However, from the viewpoint of obtaining good thermal stability and long-term strength of the polyethylene resin composition, trace amounts of calcium are inevitably mixed in.

[0101] That is, if the amount of neutralizing agent added to the polyethylene resin obtained by polymerization using Ziegler catalyst is insufficient, catalyst residues may still exist in the resin in an active state, which may reduce the thermal stability or long-term strength of the polyethylene resin composition.

[0102] Therefore, in this embodiment, the minimum amount of neutralizing agent required to neutralize the catalyst residue must be added. Considering the above, the calcium concentration of the polyethylene resin layer 21 is 10 ppm or more, preferably 13 ppm or more, more preferably 15 ppm or more, and even more preferably 20 ppm or more.

[0103] From the viewpoint of ensuring thermal stability, the oxidation induction time (OIT) of the polyethylene resin layer 21 at 210°C is preferably 20 minutes or more. If the oxidation induction time at 210°C is less than 20 minutes, there is a risk of resin deterioration during heat processing of the polyethylene resin, resulting in a decrease in long-term strength or an increase in particles originating from deterioration, which is not preferred in this embodiment.

[0104] Thermostatic creep test is widely used as a method for evaluating the long-term strength of piping materials using polyethylene resin. To fully ensure the long-term strength of piping materials for ultrapure water, regarding the thermostatic creep performance of the polyethylene resin layer 21 when it is formed into piping material, it is preferable that the piping material can withstand a circumferential stress of 5.0 MPa at 80°C for more than 3000 hours without failure.

[0105] The material properties of the polyethylene resin composition are more preferably those of pressure resistance of "PE100" or higher as described in ISO 9080, ISO 1167, and ISO 12162 standards. It should be noted that "PE100" refers to polyethylene that, in a thermal internal pressure creep test, has its stress-failure time curve measured at three different temperature levels with a difference of more than 50°C between the highest and lowest temperatures, for at least 9000 hours. The minimum guaranteed stress value after 50 years of maintenance at 20°C is estimated by extrapolation using a multiple correlation average, and the resulting LPL (lower prediction limit) value is 10 MPa or higher and 11.19 MPa or lower in the classification table specified in ISO 12162.

[0106] The polyethylene resin layer 21 may or may not contain antioxidants. It should be noted that examples of antioxidants include phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, aromatic amine antioxidants, and lactone antioxidants.

[0107] Examples of phenolic antioxidants include: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethyl bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 3,5-bis(1,1-dimethylethyl)-4-hydroxy-C7-C9 alkyl ester of phenylpropionate, and 3... ,3',3”,5,5',5”-Hexa-tert-butyl-a,a',a”-(trimethylbenzyl-2,4,6-triyl)tri-p-cresol, 4,6-bis(dodecylthiomethyl)o-cresol, 4,6-bis(octylthiomethyl)o-cresol, ethyl bis(oxyethyl)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-ditert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-ditert-butyl-4-hydroxybenzyl)-1,3,5-tri -2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-dimethyl)methyl]-1,3,5-tris -2,4,6(1H,3H,5H)-trione, 2,6-ditert-butyl-4-[4,6-di(octylthio)-1,3,5-trione] [2-ylamino]phenol, and [{3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl}methyl]diethyl phosphate, etc.

[0108] When using phenolic antioxidants, one type can be used alone, or two or more can be used in combination. From the viewpoint of preventing calcium dissolution, it is preferable that they do not contain oxygen derived from groups other than phenolic groups. Examples include: 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(trimethylbenzene-2,4,6-triyl)tri-p-cresol, 2,6-di-tert-butyl-4-[4,6-di(octylthio)-1,3,5-trimethylbenzene-2,4,6-trimethylbenzene-2,6-trimethylbenzene-4-[4,6-di(octylthio)-1,3,5-trimethylbenzene-2,6 ... [2-ylamino]phenol, 4,4',4”-(1-methylpropane-3-ylidene)tris(6-tert-butyl-m-cresol), and 6,6'-di-tert-butyl-4,4'-butylidene bis-m-cresol, etc. Furthermore, when using phenolic antioxidants with oxygen derived from groups other than phenolic groups as antioxidants, the calcium concentration in the polyethylene resin is preferably 50 ppm or less. It should be noted that examples of functional groups with oxygen derived from groups other than phenolic groups include: ester groups, carbonyl groups, carboxyl groups, ether groups, nitro groups, nitroso groups, amide groups, oxoazo groups, sulfonyl groups, etc.

[0109] Examples of phosphorus-based antioxidants include: tris(2,4-di-tert-butylphenyl) phosphite, tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxan-6-yl]oxy]ethyl]amine, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl phosphite, and tetra(2,4-di-tert-butylphenyl)(1,1-biphenyl)-4,4'-diyl bisphosphite, etc.

[0110] Examples of sulfur-based antioxidants include: dilaurate thiodipropionate, dimyristyl thiodipropionate, distearate thiodipropionate, and pentaerythritol tetra(3-lauryl thiopropionate).

[0111] Examples of aromatic amine antioxidants include monoamine compounds such as diphenylamine compounds, quinoline compounds, and naphthylamine compounds, as well as diamine compounds such as phenylenediamine compounds and benzimidazole compounds.

[0112] Examples of diphenylamine compounds include p-(p-toluenesulfonamide)-diphenylamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, and 4,4'-dioctyldiphenylamine derivatives.

[0113] Examples of quinoline compounds include 2,2,4-trimethyl-1,2-dihydroquinoline polymers.

[0114] Examples of naphthylamine compounds include phenyl-α-naphthylamine and N,N'-bis(2-naphthyl)-p-phenylenediamine.

[0115] Examples of phenylenediamine compounds include: N-N'-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-phenyl-N'-(3-methacryloyloxy-2-hydroxypropyl)-p-phenylenediamine, N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, mixtures of N-N'-diphenyl-p-phenylenediamine, diaryl-p-phenylenediamine derivatives or mixtures thereof.

[0116] Examples of benzimidazole compounds include: 2-mercaptobenzimidazole, 2-mercaptomethylbenzimidazole, zinc salts of 2-mercaptobenzimidazole, and zinc salts of 2-mercaptomethylbenzimidazole.

[0117] Examples of lactone antioxidants include the reaction products of 3-hydroxy-5,7-ditert-butylfuran-2-one and o-xylene.

[0118] From the viewpoint of ensuring preferred strength by suppressing the influence of oxygen, the content of antioxidant in the polyethylene resin layer 21 can be, for example, 0.01% by weight or more, preferably 0.03% by weight or more, more preferably 0.05% by weight or more. The upper limit of the antioxidant content can be, for example, 5% by weight or less, preferably 1% by weight or less, more preferably 0.5% by weight or less.

[0119] The polyethylene resin layer 21 may or may not contain a light stabilizer; from the viewpoint of preventing the leaching of total organic carbon (TOC), it is preferable to be free of a light stabilizer. It should be noted that hindered amine light stabilizers (HALS) can be cited as examples of light stabilizers. Furthermore, the polyethylene resin layer 21 of this embodiment is preferably substantially free of a light stabilizer. Here, "substantially free" means that no light stabilizer is actively added, allowing it to inevitably mix in as an impurity. The lower the concentration of the light stabilizer that inevitably mixes in as an impurity, the better, for example, below 600 ppm. This value of 600 ppm is estimated based on the examples and comparative examples shown in Table 3 below, corresponding to an allowable amount of TOC leaching of 30,000 μg / m³. 2The HALS values ​​are shown below. Specifically, the average TOC dissolution rate of 0 ppm in Examples 1, 3, and 4 (Table 3) is 6500 μg / m³. 2 Compared to Comparative Example 1, where the HALS addition was 1000 ppm and the TOC dissolution value was 46000 μg / m³, this figure is different from that of Comparative Example 1. 2 The relationship is connected by a straight line, which is estimated to be equivalent to a TOC dissolution rate of 30,000 μg / m³. 2 The amount of HALS added was calculated to obtain 600ppm.

[0120] Examples of hindered amine light stabilizers include: NH-type hindered amine compounds, NR-type hindered amine compounds, and N-OR-type hindered amine compounds.

[0121] Examples of NH-type hindered amine compounds include: Tinuvin 770DF, Chimassorb 2020FDL, Chimassorb 944FDL (all trade names, manufactured by BASF), Adekastab LA-68, Adekastab LA-57 (both trade names, manufactured by ADEKA), Cyasorb UV-3346, and Cyasorb UV-3853 (both trade names, manufactured by SunChemical).

[0122] Examples of hindered amine compounds of the NR type include: Tinuvin 622SF, Tinuvin 765, Tinuvin PA144, Chimassorb 119, Tinuvin 111 (all trade names, manufactured by BASF), Sabostab UV119 (trade name, manufactured by SABO), Adekastab LA-63P, and Adekastab LA-52 (all trade names, manufactured by ADEKA).

[0123] Examples of N-OR type hindered amine compounds include: Tinuvin 123, Tinuvin 5100, TinuvinNOR371FF, and Flamesterab NOR116FF (all trade names, manufactured by BASF).

[0124] The polyethylene resin layer 21 may or may not contain a UV absorber (UVA). It should be noted that examples of UV absorbers include: benzophenone-based UV absorbers, salicylate-based UV absorbers, benzoic acid ester-based UV absorbers, benzotriazole-based UV absorbers, cyanoacrylate-based UV absorbers, quenchers, etc. For polyethylene or polypropylene, benzophenone-based UV absorbers and benzotriazole-based UV absorbers are particularly preferred.

[0125] Examples of benzophenone-based ultraviolet absorbers include 2-hydroxy-4-methoxybenzophenone.

[0126] Examples of benzotriazole-based ultraviolet absorbers include: 2-(2-hydroxy-5-methylphenyl)benzotriazole (Sumisorb 200, manufactured by Sumika Chemtex), 2-(2-hydroxy-5-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole (Tinuvin 326, manufactured by BASF), 2-(2-hydroxy-3,5-ditert-butylphenyl)-5-chlorobenzotriazole (Tinuvin 327, manufactured by BASF), and 2-(2-hydroxy-3,5-ditert-pentylphenyl)benzotriazole (Tinuvin 328, manufactured by BASF).

[0127] From the viewpoint of achieving good rigidity of the polyethylene resin composition, the density of the polyethylene resin composition of the polyethylene resin layer 21 can be cited as an example: preferably 0.946 g / cm³. 3 The above, more preferably 0.947 g / cm³ 3 The above is further optimized to be 0.948 g / cm³. 3 That's all. Furthermore, from the viewpoint of achieving good long-term durability and flexibility in polyethylene resin compositions, the aforementioned density can be cited as preferably 0.960 g / cm³. 3 The preferred value is 0.957 g / cm³. 3 The following is a further preferred value: 0.953 g / cm³ 3 The density is based on the value established in JIS K6922-2:1997.

[0128] The melt flow rate (MFR) of the polyethylene resin composition in polyethylene resin layer 21 at a temperature of 190°C and a load of 21.6 kg. 21.6 Examples include 6g / 10 minutes or more and 25g / 10 minutes or less. From the viewpoint of achieving good processability of the polyethylene resin composition, this MFR... 21.6Examples of suitable resin strength include 8g / 10 minutes or more, more preferably 12g / 10 minutes or more, and even more preferably 15g / 10 minutes or more. Furthermore, from the viewpoint of achieving good long-term durability of the resin, this MFR... 21.6 Examples of preferred values ​​include 22g / 10 minutes or less, and more preferably 20g / 10 minutes or less. MFR 21.6 The value is based on JIS K6922-2:1997.

[0129] The smoothness (arithmetic mean roughness Ra) of the inner surface of the polyethylene resin layer 21 is not particularly limited, for example, it can be 0.50 μm or less. In order to obtain good low leaching properties of the piping, the smoothness of the inner surface of the polyethylene resin layer 21 is preferably 0.40 μm or less, more preferably 0.35 μm or less.

[0130] When a coating resin layer 22 is provided on the outer side of the innermost polyethylene resin layer 21 forming the inner surfaces 11a, 31a to 35a, 42a (an example of the inner surface of the piping material) of the ultrapure water piping material, the thickness of the innermost polyethylene resin layer 21 is preferably 0.3 mm or more, more preferably 0.4 mm or more, taking into account the overall strength of the ultrapure water piping material and the calcium concentration contained in the coating resin layer 22. The upper limit of the thickness is preferably 2.0 mm or less, more preferably 1.5 mm or less.

[0131] When a covering resin layer 22 is not provided on the outer side of the polyethylene resin layer 21 on the inner surface 10a, 31a to 35a, 42a (an example of the inner surface of the piping material) of the ultrapure water piping material, the thickness of the polyethylene resin layer 21 is not particularly limited, and for example, 0.3 mm or more can be given as the lower limit of the thickness.

[0132] [Coated Resin Layer]

[0133] The type of coating resin layer 22 is not particularly limited. It can be a polyethylene resin layer containing polyethylene resin, a gas barrier resin layer containing gas barrier resin, or a combination thereof.

[0134] When a polyethylene resin layer is provided as the coating resin layer 22, the polyethylene resin can be appropriately selected from the polyethylene resin composition that is the main component of the innermost polyethylene resin layer 21.

[0135] Among these considerations, high-density polyethylene (HDPE) is preferred, taking into account the inhibition of leaching of low molecular weight components and / or the durability when cleaning piping with chemicals.

[0136] The polyethylene resin that is the main component of the polyethylene resin layer 22 can be the same type as or different from the polyethylene resin composition that is the main component of the innermost polyethylene resin layer 21. When the two layers are in contact with each other and are stacked, from the viewpoint of improving the adhesion between the two layers and making them exhibit preferred strength, it is more preferable to use the same type of polyethylene resin.

[0137] The polyethylene resin layer in the coating resin layer 22 preferably contains an antioxidant. Examples of antioxidants include phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, aromatic amine antioxidants, and lactone antioxidants. From the viewpoint of ensuring preferred strength by suppressing the effects of oxygen, the antioxidant content in the polyethylene resin layer 22 is, for example, 0.01% by weight or more, preferably 0.1% by weight or more. The upper limit for the antioxidant content is, for example, 5% by weight or less, preferably 1% by weight or less, and more preferably 0.5% by weight or less.

[0138] When an air barrier layer is provided as the coating resin layer 22, the air barrier layer can be stacked on the outside of the innermost polyethylene resin layer 21. The air barrier layer can form the outermost layer of the piping material for ultrapure water (e.g., pipe 11), or other layers can be provided on the outside of the air barrier layer.

[0139] By providing a gas barrier layer, the dissolution of gases in ultrapure water can be effectively suppressed, therefore, providing a gas barrier layer is preferable. In addition, since the gas barrier layer prevents oxygen from the outer surface 11b of the ultrapure water piping material (e.g., pipe 11) from penetrating to the innermost polyethylene resin layer 21, or penetrating to the interior of the outer polyethylene resin layer provided as needed, it can also improve the long-term strength of the ultrapure water piping material (e.g., pipe 11).

[0140] By providing a gas barrier layer, oxygen from the outer surface 11b of the ultrapure water piping material (e.g., pipe 11) is prevented from permeating to the innermost polyethylene resin layer 21, or to the interior of the outermost polyethylene resin layer, which is provided as needed. This improves the strength of the ultrapure water piping material (e.g., pipe 11). Furthermore, providing a gas barrier layer is also preferable in terms of effectively suppressing the dissolution of gases in ultrapure water.

[0141] Materials used as the gas barrier layer include, for example, polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), polyvinylidene chloride resin (PVDC), and polyacrylonitrile (PAN), with polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH) being preferred.

[0142] The thickness of the gas barrier layer is not particularly limited as long as it is sufficient to ensure the gas barrier properties of the polyethylene resin. For example, 30 to 300 μm is acceptable, 50 to 250 μm is preferred, and 70 to 250 μm is even more preferred.

[0143] Applications of piping materials for ultrapure water

[0144] The piping material for ultrapure water according to embodiments of the present invention is used for conveying ultrapure water. Specifically, the piping material for ultrapure water according to embodiments of the present invention can be used as piping within an ultrapure water manufacturing apparatus, piping for conveying ultrapure water from the ultrapure water manufacturing apparatus to the point of use, and piping for transporting ultrapure water back from the point of use. It should be noted that ultrapure water in the present invention is defined as having a resistivity of 10 MΩ·cm or more at 25°C, more strictly defined as having a resistivity of 15 MΩ·cm or more at 25°C, and particularly strictly defined as having a resistivity of 18 MΩ·cm or more at 25°C.

[0145] The piping material for ultrapure water in embodiments of the present invention is preferably piping for nuclear power generation water where the requirements for ultrapure water quality are particularly stringent, or preferably ultrapure water delivery piping used in the manufacturing process of pharmaceuticals, or ultrapure water delivery piping used in wet processing steps such as cleaning in the manufacturing process of semiconductor components or liquid crystals, more preferably ultrapure water delivery piping used in the manufacturing process of semiconductor components. As for the semiconductor component, a component with higher integration is preferred; specifically, it is more preferably used in the manufacturing process of semiconductor components with a minimum linewidth of 65 nm or less. For example, SEMI F75 can be cited as a relevant standard for the quality of ultrapure water used in semiconductor manufacturing.

[0146] Furthermore, since the piping material for ultrapure water according to embodiments of the present invention has a polyethylene resin layer, it exhibits excellent workability. For example, it can be easily fused at relatively low temperatures, such as butt welding or EF (electrofusion) welding.

[0147] Manufacturing of piping materials for ultrapure water

[0148] The ultrapure water piping material of the present invention can be manufactured by preparing a polyethylene resin as the main component of the polyethylene resin layer 21 forming the inner surfaces 10a, 11a, 31a to 35a, 42a of the piping material, and preparing a coating resin constituting the outer coating resin layer 22 as needed, and co-extruding the materials in such a way that the thickness of each layer is a specific thickness. Since the ultrapure water piping material of the present invention is made of polyethylene resin, it can be manufactured at a lower cost.

[0149] Example

[0150] The present invention will be further described in detail below with reference to embodiments, but the present invention is not limited to these embodiments.

[0151] [Examples 1-4] [Comparative Examples 1-2]

[0152] Prepare the following materials and conduct the following assessment.

[0153] (Antioxidants)

[0154] Irganox 1010 (manufactured by BASF Japan)

[0155] Irganox 1330 (manufactured by BASF Japan)

[0156] Figure 5 A diagram showing the structural formula of Irganox1010. Figure 6 A diagram showing the structural formula of Irganox 1330.

[0157] (1) Polymerization of polyethylene resins

[0158] (Preparation of solid catalyst components)

[0159] Under a nitrogen atmosphere, 20 g of commercially available magnesium ethoxide (average particle size 860 μm), 1.66 g of granular aluminum trichloride, and 2.72 g of diphenyldiethoxysilane were added to a 1 L container (for grinding) containing approximately 700 magnetic beads with a diameter of 10 mm. The mixture was then co-ground for 3 hours using a vibratory ball mill at an amplitude of 6 mm and a vibration frequency of 30 Hz. After co-grinding, the contents were separated from the magnetic beads under a nitrogen atmosphere.

[0160] 5 g of the co-pulverized product obtained as described above and 20 ml of n-heptane were added to a 200 ml three-necked flask. While stirring, 10.4 ml of titanium tetrachloride was added dropwise at room temperature, and the temperature was raised to 90 °C, with stirring continued for 90 minutes. Then, the reaction system was cooled, the supernatant was extracted, and n-hexane was added. This operation was repeated three times. The resulting pale yellow solid was dried at 50 °C under reduced pressure for 6 hours to obtain the solid catalyst component.

[0161] (Preparation of the polyethylene resin composition)

[0162] In a 100L first polymerization liquid-filled ring reactor, dehydrated and purified isobutane is continuously fed at a rate of 63L / hr, triisobutylaluminum is continuously fed at a rate of 20g / hr, the aforementioned solid catalyst is continuously fed at a rate of 3.6g / hr, and ethylene is continuously fed at a rate of 7kg / hr, thereby achieving the target MFR. 21.6The method of controlling the comonomer content involved adding hydrogen (to control the MFR) and 1-hexene as a comonomer (to control the amount of α-olefin). Ethylene and 1-hexene were copolymerized at 85°C, a polymerization pressure of 4.3 MPa, and an average residence time of 0.9 hr. A portion of the polymerization product was collected, and its physical properties were determined. The results showed that the MFR... 21.6 The concentration was 0.2 g / 10 minutes, and the α-olefin content was 1.2 mol%.

[0163] Then, the isobutane slurry containing the polymerization products of the first step was directly and completely introduced into a 200L second-step reactor without adding catalyst. Isobutane was supplied at a rate of 40L / hr, and ethylene at a rate of 7kg / hr. The second-step polymerization was carried out at 85°C, a polymerization pressure of 4.2MPa, and an average residence time of 0.9hr. In this second step, hydrogen and 1-hexene were supplied in a manner that produced a polymer substantially the same as in the first step. A portion of the polymerization products after the second step was collected, and its physical properties were determined. The MFR was... 21.6 The concentration was 0.2 g / 10 minutes, and the α-olefin content was 1.2 mol%.

[0164] Then, the isobutane slurry containing the polymerization products of the second step is directly and completely introduced into a 400L third-step reactor without adding catalyst or 1-hexene. Isobutane is continuously supplied at a rate of 87L / hr, and ethylene is continuously supplied at a rate of 18kg / hr, thereby achieving the target MFR. 21.6 Hydrogen was supplied in a specific manner, and the third-step polymerization was carried out at 90°C, a polymerization pressure of 4.1 MPa, and an average residence time of 1.5 hr. The polyethylene polymer discharged from the third-step reactor was dried, specific additives were added to the obtained polymer powder, and the mixture was melt-kneaded to obtain a polyethylene resin composition. The MFR of this polyethylene resin composition was measured, and the results showed... 21.6 It has a strength of 18g / 10 minutes and a density of 0.951g / cm³. 3 The α-olefin content is 0.5 mol%. It should be noted that the ratio of polymer (high molecular weight component (A)) produced in both the first and second steps is 20 by weight.

[0165] On the other hand, the MFR of the low molecular weight component (B) polyethylene polymer produced in the third step was determined by further polymerization under the polymerization conditions of the third step, and the MFR was 130 g / 10 min. Furthermore, the α-olefin content of the low molecular weight component polyethylene polymer produced in the third step was determined by making the additivity of the α-olefin content after the third step with respect to the α-olefin content after the second step hold, and it was 0.1 mol%. The results are shown in (Table 1).

[0166] The polymers produced in the first and second steps are collectively designated as high molecular weight components (A), and the polymers produced in the third step are designated as low molecular weight components (B).

[0167] [Table 1]

[0168]

[0169] (2) Fabrication of polyethylene resin composite sheets

[0170] In this embodiment, various evaluations are performed in sheet form rather than in tube shape.

[0171] Based on the composition shown in Table 2 below, polyethylene resin particles were hot-pressed at 200°C for 3 minutes to form sheets of 180mm*180mm*1mm, thus obtaining test samples.

[0172] (3) Calcium concentration assessment

[0173] After cutting the above-mentioned sheet to prepare a 0.1g test piece, it was fed into a microwave decomposition system (MARS6, manufactured by CEM Corporation) along with 6mL of nitric acid, and the test piece was decomposed by microwave. After decomposition, 1mL of hydrogen peroxide was added, followed by ultrapure water, and the volume was adjusted to 25mL. The calcium concentration of the solution was measured using an ICP (Inductively Coupled Plasma) device (SPS5100, manufactured by SII Technology Corporation), and the calcium concentration of the polyethylene resin composition sheet was calculated.

[0174] (4) Calcium dissolution assessment

[0175] Prepare three samples, each cut from the aforementioned sheet into 30mm x 50mm pieces. Wash the samples with ultrapure water using a method based on the SEMI F40 standard. Then, seal the samples together with 100mL of ultrapure water into a PFA container. The PFA container is then left to stand at 85℃±5℃ for 7 days to allow dissolution. The amount of calcium dissolved is then determined using an ICP-MS (Inductively Coupled Plasma Mass Spectrometry) instrument (Agilent Technologies, Model Agirent 7500cs). It should be noted that the baseline value for calcium dissolution is set at 15μg / m³. 2 The results are shown in Table 2.

[0176] (5) Oxidation Induction Time (OIT) Assessment

[0177] The oxidation induction time (OIT) of the above-mentioned sheet was determined using a differential scanning calorimeter (DSC). A DSC7020 manufactured by Seiko Electronics Co., Ltd. was used for the measurement. After placing 5 mg of sheet into the furnace, the middle cover was closed, and nitrogen was flowed into the furnace at a rate of 50 mL / min while the temperature was increased to 210°C at a rate of 20°C / min. This temperature was then maintained for 5 minutes. After standing, the nitrogen was replaced with oxygen to oxidize the sample. The oxidation induction time was determined by calculating the time from the time of nitrogen replacement to the rise of the exothermic peak due to oxidation. It should be noted that the baseline value for the oxidation induction time was set to be 20 minutes or more.

[0178] The oxidation induction time is closely related to the thermal stability or long-term strength of the sample; the longer the oxidation induction time, the better the thermal stability or long-term strength. The results are shown in Table 2.

[0179] [Table 2]

[0180]

[0181]

[0182] As shown in the table above, when the calcium concentration of the polyethylene resin composition sheet is between 10 ppm and 60 ppm (Examples 1-4), the calcium leaching amount is less than 15 μg / m³. 2 It can effectively inhibit calcium dissolution and also exhibits thermal stability.

[0183] On the other hand, when the calcium concentration of the polyethylene resin composition sheet is 60 ppm or higher (Comparative Example 1), the calcium leaching amount exceeds 15 μg / m³. 2 .

[0184] Furthermore, by comparing Examples 1 and 3, and Examples 2 and 4, it can be seen that, although the calcium concentration in the polyethylene resin is the same, the addition of Irganox 1330 as a phenolic antioxidant is more effective in inhibiting calcium dissolution than the addition of Irganox 1010. The reason for this is speculated as follows.

[0185] In other words, because Irganox 1010 contains oxygen atoms other than phenolic groups in its molecule, its molecular polarity is relatively high, making it easily soluble in polyethylene resins. Furthermore, the high polarity of Irganox 1010 may lead to intermolecular forces interacting easily with calcium components, potentially causing calcium to dissolve as Irganox 1010 dissolves. That is, it can be considered that adding Irganox 1010 will also make calcium components more easily soluble.

[0186] On the other hand, Irganox 1330 is a low-polarity molecule without oxygen derived from phenolic groups, suggesting that it does not participate in the dissolution of calcium components.

[0187] Based on the above results, when adding phenolic antioxidants, from the viewpoint of reducing calcium dissolution, it is preferable that the antioxidant does not have oxygen originating from sources other than phenolic groups.

[0188] Furthermore, it can be seen that when using phenolic antioxidants with oxygen derived from sources other than phenolic groups as antioxidants, the calcium concentration in polyethylene resins is preferably below 50 ppm.

[0189] As shown in Comparative Example 2, when the calcium concentration of the polyethylene resin composition synthesized using the Ziegler catalyst was below 10 ppm, although calcium dissolution was suppressed, the oxidation induction time was less than 20 minutes, resulting in insufficient thermal stability. This can be attributed to the fact that the Ziegler catalyst remaining in the resin after polymerization was not adequately neutralized, leaving active catalyst residue and reducing thermal stability. Therefore, when using polyethylene resin synthesized using the Ziegler catalyst as piping material for ultrapure water, a calcium concentration of 10 ppm or higher is required to exhibit thermal stability.

[0190] (6) TOC dissolution

[0191] Prepare three samples, each cut from the aforementioned sheet into 30mm x 50mm pieces. Wash the samples with ultrapure water using a method based on SEMI F40 standard. Then, seal the samples together with 100mL of ultrapure water into a PFA container. The PFA container is then left to stand at 85℃±5℃ for 7 days to allow dissolution. The TOC dissolution amount is then determined using a total organic carbon analyzer (Shimadzu Corporation, model TOC-5000). It should be noted that the benchmark value for TOC dissolution is set as the requirement for TOC dissolution described in SEMI F57 standard (60000μg / m³). 2 (The following) half of the value, i.e., 30000 μg / m 2 The results are shown in Table 3.

[0192] In Table 3, the sheet test samples from Examples 1, 3, and 4 shown in Table 2 without HALS were used, and the sheet test sample from Comparative Example 1 with HALS added according to the composition shown in Table 3 were used.

[0193] [Table 3]

[0194]

[0195] As shown in Table 3, according to Example 1 and Comparative Example 1, the TOC leaching amount exceeds the baseline value when a light stabilizer is included. Furthermore, according to Examples 1, 3, and 4, the TOC leaching amount remains within the baseline value regardless of the type of phenolic antioxidant when no light stabilizer is present.

[0196] [Examples 5-8]

[0197] Using the polyethylene resin compositions listed in Table 1, piping materials (elbows, pipes) were formed, and the following evaluations were performed. The following describes the tests in detail, but the invention is not limited to these examples.

[0198] (1) Elbow assessment

[0199] (1-1) Forming of the elbow

[0200] Based on the composition shown in Table 4, an elbow with a diameter of 25A (refer to Table 4) is manufactured by injection molding. Figure 3B Forming. Elbows are formed using common forming methods.

[0201] (1-2) Calcium concentration assessment

[0202] After cutting the aforementioned elbow to prepare a 0.1g test piece, it was fed into a microwave decomposition system (MARS6, manufactured by CEM Corporation) along with 6mL of nitric acid. The test piece was decomposed by microwaves. After decomposition, 1mL of hydrogen peroxide was added, followed by ultrapure water, and the volume was adjusted to 25mL. The calcium concentration of the solution was measured using an ICP device (SPS5100, manufactured by SII Technology Corporation), and the calcium concentration of the polyethylene resin elbow was calculated.

[0203] (1-3) Assessment of calcium dissolution

[0204] After washing the elbow samples with ultrapure water according to the SEMI F40 standard, 80 mL of ultrapure water was added to the elbows, and the ends were sealed. The elbows were then left to stand at 85℃±5℃ for 7 days to allow for leaching. The amount of calcium leached was then determined using an ICP-MS apparatus (Agilent Technologies, model Agirent 7500cs).

[0205] (1-4) Oxidation Induction Time (OIT) Assessment

[0206] The oxidation induction time (OIT) of the above-mentioned elbow was determined using a differential scanning calorimeter (DSC). A DSC7020 manufactured by Seiko Electronics Co., Ltd. was used for the measurement. After placing a 15 mg cut blade of the elbow into the furnace, the middle cover was closed, and nitrogen was flowed into the furnace at a rate of 50 mL / min while the temperature was increased to 210°C at a rate of 20°C / min. The furnace was then allowed to stand for 5 minutes. After standing, the nitrogen was replaced with oxygen to oxidize the sample. The oxidation induction time was determined by calculating the time from the time of nitrogen replacement to the rise of the exothermic peak due to oxidation. It should be noted that the baseline value for the oxidation induction time was set to be 20 minutes or more.

[0207] (1-5) Thermal internal pressure creep test

[0208] The test was conducted according to the PTC K 03:2010 standard for polyethylene pipe systems for water distribution (PTC K 03:2010 "Polyethylene pipes for tap water distribution"). The elbow was filled with water, the ends were fixed with a sealing fixture, and then immersed in a warm water bath at 80°C. A circumferential stress of 5.0 MPa was applied, and the elbow was left to stand in the warm water bath.

[0209] [Table 4]

[0210]

[0211]

[0212] As shown in the table above, when using a polyethylene resin composition with a calcium concentration of 10 ppm to 60 ppm to form the piping material, the calcium leaching amount is less than 15 μg / m. 2 It can effectively inhibit calcium dissolution and also exhibits thermal stability.

[0213] Furthermore, the piping material exhibits excellent thermal creep resistance at 80°C and 5.0 MPa for 3000 hours without damage. It is believed that the Ziegler catalyst remaining in the polyethylene resin composition after polymerization is sufficiently neutralized, resulting in long-term strength.

[0214] (2) Management Assessment

[0215] (2-1) Tube Forming

[0216] Based on the composition shown in Table 5, a tube with an outer diameter of 32 mm and a wall thickness of 3 mm was formed by extrusion molding. The tube was formed using a commonly used forming method.

[0217] (2-2) Calcium concentration assessment

[0218] After cutting the tube to prepare a 0.1g sample, it was fed into a microwave decomposition system (MARS6, CEM) along with 6mL of nitric acid. The sample was then decomposed using microwaves. After decomposition, 1mL of hydrogen peroxide was added, followed by ultrapure water, and the volume was adjusted to 25mL. The calcium concentration of the solution was measured using an ICP device (SPS5100, SII Technology) to calculate the calcium concentration of the polyethylene resin tube.

[0219] (2-3) Assessment of calcium dissolution

[0220] The tube samples were washed with ultrapure water using a method based on the SEMI F40 standard. 90 mL of ultrapure water was then added to the tubes, and the ends were sealed. The tubes were then left to stand at 85℃±5℃ for 7 days to allow dissolution. The amount of calcium dissolved was then determined using an ICP-MS apparatus (Agilent Technologies, Model Agirent 7500cs).

[0221] (2-4) Oxidation Induction Time (OIT) Assessment

[0222] The oxidation induction time (OIT) of the above-mentioned tubes was determined using a differential scanning calorimeter (DSC). A DSC7020 manufactured by Seiko Electronics Co., Ltd. was used for the measurement. After adding 15 mg of the inner layer cutting material to the furnace, the middle cover was closed, and nitrogen was flowed into the furnace at a rate of 50 mL / min while the temperature was increased to 210°C at a rate of 20°C / min. The furnace was then allowed to stand for 5 minutes. After standing, the nitrogen was replaced with oxygen to oxidize the sample. The oxidation induction time was determined by calculating the time from the time of nitrogen replacement to the rise of the exothermic peak due to oxidation. It should be noted that the baseline value for the oxidation induction time was set to be 20 minutes or more.

[0223] (2-5) Thermal internal pressure creep test

[0224] The test was conducted according to the PTC K 03:2010 standard for polyethylene pipe systems for water distribution (PTC K 03:2010 "Polyethylene pipes for tap water distribution"). The pipe was filled with water, the ends were fixed with a sealing fixture, and then immersed in a warm water bath at 80°C. A circumferential stress of 5.0 MPa was applied, and the pipe was left to stand in the warm water bath.

[0225] [Table 5]

[0226]

[0227] As shown in the table above, when using a polyethylene resin composition with a calcium concentration of 10 ppm to 60 ppm to form the piping material, the calcium leaching amount is less than 15 μg / m. 2It can effectively inhibit calcium dissolution and also exhibits thermal stability. Furthermore, the piping material shows no damage in thermal internal pressure creep performance for 3000 hours at 80°C and 5.0 MPa. It is believed that the Ziegler catalyst remaining in the resin composition after polymerization of the polyethylene resin composition is fully neutralized, exhibiting long-term strength.

[0228] [Examples 9-13][Comparative Examples 3-8]

[0229] In accordance with Example 1, polyethylene resin compositions (Table 6) and (Table 7) were prepared and evaluated as follows.

[0230] (4) Tube forming

[0231] Based on the polyethylene resin composition shown in Tables 6 and 7, tubes with an outer diameter of 110 mm and a wall thickness of 10 mm are formed. The tubes are formed using commonly used forming methods.

[0232] It should be noted that Examples 10-13 and Comparative Examples 3-8 were manufactured using the same catalyst, the same polymerization process, the same α-olefin, and the additives of Example 3 as Example 9 (Table 1), with the amount of hydrogen, the amount of α-olefin, and the ratio of each component adjusted only in the manner shown in Table 6 and Table 7.

[0233] (5) Assessment of slow-speed crack growth

[0234] The notched tube test was conducted according to ISO 13479 at a test temperature of 80°C and a test pressure of 9.2 bar. The test results are shown in Tables 6 and 7.

[0235] (6) Evaluation of the smoothness of the inner surface of the tube

[0236] Cut the formed tube in half and observe the condition of the inner surface. A condition visually confirmed as having obvious unevenness and no gloss is rated "×", a condition with a certain degree of gloss is rated "○", and a condition with good gloss is rated "◎". The test results are shown in (Table 6) and (Table 7).

[0237] (7) Judgment of the tube

[0238] For low-speed crack growth assessment, tubes with a test result of >500 hours and an inner surface smoothness assessment of "◎~○" are considered "suitable". All other results are considered "unsuitable".

[0239] [Table 6]

[0240]

[0241] [Table 7]

[0242]

[0243] As shown in the table above, pipes formed using the polyethylene resin compositions of the present invention simultaneously satisfy both low-speed crack growth resistance and inner surface smoothness. In contrast, pipes using polyethylene resin compositions other than those of the present invention struggle to achieve both low-speed crack growth resistance and inner surface smoothness. Furthermore, using the polyethylene resin compositions of Examples 9-13, with antioxidants formulated according to the formulations of Examples 1 or 3, and evaluating their performance, the results showed that the calcium dissolution rate and oxidation induction time at 210°C exhibited the same performance as in Examples 1 or 3, enabling the manufacture of excellent and high-quality piping materials for ultrapure water.

[0244] Symbol Explanation

[0245] 10, 11: pipe

[0246] 10a, 11a: Inner surface

[0247] 10b, 11b: Outer surface

[0248] 21: Polyethylene resin layer (an example of a layer)

[0249] 22: Coated resin layer

Claims

1. A piping material for ultrapure water, comprising a layer primarily composed of polyethylene resin, and The layer forms the inner surface of the piping material. The calcium concentration in the layer is between 10 ppm and 60 ppm. in, The layer contains antioxidants, which include phenolic antioxidants that do not have oxygen derived from sources other than phenolic groups.

2. The piping material for ultrapure water according to claim 1, wherein, The polyethylene resin is a polyethylene resin obtained by polymerization using a Ziegler catalyst.

3. The piping material for ultrapure water according to claim 1 or 2, wherein, The antioxidant comprises a phenolic antioxidant having oxygen derived from sources other than phenolic groups, and the calcium concentration in the layer is below 50 ppm.

4. The piping material for ultrapure water according to claim 1 or 2, wherein, The layer does not contain any light stabilizer.

5. The piping material for ultrapure water according to claim 1 or 2, wherein, The oxidation induction time of the layer at 210°C is more than 20 minutes.

6. The piping material for ultrapure water according to claim 1 or 2, wherein, The total amount of organic carbon dissolved from the layer is 30,000 μg / m³. 2 the following.

7. The piping material for ultrapure water according to claim 1 or 2, wherein, The thickness of the layer is 0.3 mm or more.

8. The piping material for ultrapure water according to claim 1 or 2, wherein, The thickness of the layer is less than 2.0 mm.

9. The piping material for ultrapure water according to claim 1 or 2, wherein, The ultrapure water piping material was subjected to a circumferential stress of 80°C and 5.0 MPa for more than 3000 hours without damage.

10. A polyethylene resin composition for piping materials used in ultrapure water, comprising a polyethylene resin, and satisfying the following properties (1) to (5): Characteristic (1): Melt flow rate (MFR) at a temperature of 190°C and a load of 21.6 kg 21.6 The dosage is 6 g / 10 minutes or more, or less than 25 g / 10 minutes. Feature (2): MFR 21.6 The ratio of the melt flow rate (MFR5) to the melt flow rate at a load of 5 kg is called FR (MFR). 21.6 / MFR5) is 25 or higher and 60 or lower; Characteristic (3): Contains high molecular weight component (A) and low molecular weight component (B), MFR of high molecular weight component (A) 21.6 The content of α-olefins other than ethylene is 0.05 g / 10 min to 1.0 g / 10 min, and the content of α-olefins other than ethylene is 0.8 mol% to 2.0 mol%, and the content ratio relative to the total resin is 35 wt% to 50 wt%. The melt flow rate (MFR) of the low molecular weight component (B) at a temperature of 190°C and a load of 2.16 kg is [not specified]. 2.16 The recommended serving size is 20 g / 10 minutes or more, or 500 g / 10 minutes or less. Characteristic (4): Density is 0.946 g / cm³ 3 Above 0.960 g / cm 3 the following; Characteristic (5): Calcium concentration is between 10 ppm and 60 ppm. in, The resin composition contains an antioxidant, which includes phenolic antioxidants that do not have oxygen derived from groups other than phenolic groups.

11. The polyethylene resin composition for ultrapure water piping materials according to claim 10, wherein, The polyethylene resin is a polyethylene resin obtained by polymerization using a Ziegler catalyst.

12. The polyethylene resin composition for ultrapure water piping materials according to claim 10 or 11, wherein, The antioxidants include phenolic antioxidants with oxygen derived from sources other than phenolic groups, and the calcium concentration is below 50 ppm.

13. The polyethylene resin composition for ultrapure water piping materials according to claim 10 or 11 is substantially free of light stabilizers.

14. The polyethylene resin composition for ultrapure water piping materials according to claim 10 or 11, wherein the oxidation induction time at 210°C is 20 minutes or more.

Citation Information

Patent Citations

  • Process for producing improved ethylenic polymer

    JP1978078287A

  • Improved preparation of ethylene polymer

    JP1979021483A

  • Preparation of improved ethylenic polymer

    JP1980071707A

  • Preparation of improved ethylenic polymer

    JP1983225105A

  • Multilayer tube

    JP2010234576A